Impact of Wide Local Excision on Melanoma Patient Survival: A Population-Based Study - Buja, Alessandra; Rugge, Massimo; Damiani, Giovanni; De Luca, Giuseppe; Zorzi, Manuel; Fusinato, Riccardo; De Toni, Chiara; Vecchiato, Antonella; Del Fiore, Paolo; Falasco, Francesca; Spina, Romina; Rossi, Carlo Riccardo; et al. (Frontiers in Public Health, 2022)
IIntroduction Promoting standardization and quality assurance (QA) in oncology on the strength of real-world data is essential to ensure better patient outcomes. Wide excision after primary tumor biopsy is a fundamental step in the therapeutic pathway for cutaneous malignant melanoma (CMM). The aim of this population-based cohort study is to assess adherence to wide local excision in a cohort of patients diagnosed with CMM and the impact of this recommended procedure on overall and disease-specific survival. Materials and Methods This retrospective cohort study concerns CMM patients diagnosed in the Veneto region (north-east Italy) in 2017, included in the high-resolution Veneto Cancer Registry, and followed up through linkage with the regional mortality registry up until February 29th, 2020. Using population-level real-world data, linking patient-level cancer registry data with administrative records of clinical procedures may shed light on the real-world treatment of CMM patients in accordance with current guidelines. After excluding TNM stage IV patients, a Cox’s regression analysis was performed to test whether the completion of a wide local excision was associated with a difference in melanoma-specific and overall survival, after adjusting for other covariates. Results No wide excision after the initial biopsy was performed in 9.66% of cases in our cohort of 1,305 patients. After adjusting for other clinical prognostic characteristics, Cox’s regression revealed that failure to perform a wide local excision raised the hazard ratio of death in terms of overall survival (HR=4.80, 95% CI: 2.05-11.22, p < 0.001) and melanoma-specific survival (HR=2.84, 95% CI: 1.04-7.76, p=0.042). Conclusion By combining clinical and administrative data, this study on real-world clinical practice showed that almost one in ten CMM patients did not undergo wide local excision surgery. Monitoring how diagnostic-therapeutic protocols are actually implemented in the real world may contribute significantly to promoting quality improvements in the management of oncological patients.